Alternaria in apples: the hidden menace. (29th March 2022) - Pavicich, María Agustina; Patriarca, Andrea
Alternaria species are responsible for several apple diseases in pre- and postharvest stages. Particularly, mouldy core is of economic relevance due to the significant losses it implies to the productive sector. Even though the infection can begin in the orchard, several postharvest practices favour the spreading of the disease in terms of severity and frequency of incidence. Cold storage for extended periods has been shown to enhance the infection. The main species associated with mouldy core are similar in different world regions, all showing a high capacity of synthesising secondary metabolites, many of which are mycotoxins or compounds of suspected toxicity. Hence, their presence in the apple core represents a threat when the fruit is destined to process. Since visual inspection remains the preferred strategy to prevent the incorporation of mouldy fruit to the process line, the risk of Alternaria toxins in apple concentrate and other by-products cannot be disregarded.